2021
DOI: 10.3390/d13060244
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Surface Structure of Aurelia solida (Scyphozoa) Polyps and Medusae

Abstract: The surface structures and mucus layers that form an interface between the epithelial layer of organisms and their external environment were studied in the bloom-forming moon jellyfish (Aurelia solida, Scyphozoa) from the northern Adriatic. The surface of the polyps revealed epithelial ciliated cells and numerous nematocysts, both non-discharged and discharged. Cilia were also the most prominent features on the surface of adult medusa, protruding from the epidermal cells and with microvilli surrounding the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…The occurrence of microbes in mucus samples was confirmed by Scanning Electron Microscopy (SEM) And Transmission Electron Microscopy (TEM) microscopy analysis; however, they have not been found on the epithelial surfaces of polyps or on the exumbrella of jellyfish (the external part of the umbrella) (Turk et al, 2021).…”
Section: Evolution Of the Mucus Layermentioning
confidence: 93%
“…The occurrence of microbes in mucus samples was confirmed by Scanning Electron Microscopy (SEM) And Transmission Electron Microscopy (TEM) microscopy analysis; however, they have not been found on the epithelial surfaces of polyps or on the exumbrella of jellyfish (the external part of the umbrella) (Turk et al, 2021).…”
Section: Evolution Of the Mucus Layermentioning
confidence: 93%
“…The speci c microbial community is assumed to be essential for the sessile life stage (28). Here, the bacteria most likely use the polyp's mucus as a source of nutrients (28,53,54). We observed that polyps with naturally associated native microbiota and sterile polyps after recolonization harbored similar microbial communities with comparable diversity, unlike the bacterial population kept in arti cial seawater (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…A study on development and phenotypic plasticity in medusae of L. lucerna and Cassiopea andromeda considered that the flow promoted by the cilia could decrease the effect of the boundary layer around the filtering structures of the oral arms (digitata) and potentially increase the filtered volume (Jordano et al, 2020), although this has yet to be tested experimentally. Turk et al (2021) described the epidermis of polyps and medusae of Aurelia solida Browne, 1905 ('Semeaeostomeae'), and mentioned different types of cilia on the epidermis of these two life forms.…”
Section: Motile Cilia In Medusozoa: Review and New Insightsmentioning
confidence: 99%
“…Turk et al . (2021) described the epidermis of polyps and medusae of Aurelia solida Browne, 1905 (‘Semeaeostomeae’), and mentioned different types of cilia on the epidermis of these two life forms.…”
Section: Motile Cilia In Medusozoamentioning
confidence: 99%
See 1 more Smart Citation